(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Examination of the calcareous microfossil from the Anisian reef limestones of the Aggtelek Mountains, northern Hungary, described as Axopora aggtelekensis by Scholz, supports the cyanobacterian nature of this organism. It is not a Hydrozoa as originally thought by Scholz. For this microfossils, occuring in Triassic shallow water carbonates the new genus Anisophytes is proposed. The differences between Anisophytes, as gregarious microfossil composed of tubes, and other similar looking organisms, like Tubiphytes, Aeolisaccus kotori Radoicic, Koivaella Tchuvashov or Proaulopora Vologdin is discussed. Anisophytes is attributed tentatively to Cyanophyceans.